Pengaruh Literasi Keuangan, Presepsi Risiko dan Behavioral Finance Terhadap Keputusan Investasi Pada Himpunan Pengusaha Muda Indonesia di Yogyakarta - Nur Anita Chandra Putry; Maria Virgilia Kesau (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose: This study aims to determine whether financial literacy, risk perception and behavioral finance influence investment decisions made by the Indonesian Young Entrepreneurs Association in Yogyakarta. Method: This study applied a quantitative approach. Young Yogyakarta entrepreneurs who met certain criteria were the subjects of this study. The purposive sampling method was used to collect a total of 130 samples from the respondents. Multiple linear regression was used to examine the data with the IBM SPSS version 23. Finding: The results of this study indicate that the variables of risk perception and behavioral finance have a positive and significant impact on investment decisions. However, financial literacy does not affect investment decisions in entrepreneurs. Novelty: This study focuses on young entrepreneurs of HIPMI members in Yogyakarta City by combining three main variables in one comprehensive framework, in contrast to previous studies that examined general investors without geographical specificity and examined each variable with the assistance of other different variables.